The Spirituality of Saint Tarcisius in the Role of Acolytes at Saint Francis Xavier Parish in Yogyakarta - Bernardus Agus Rukiyanto; Engelbertha E. Beyda (Proceedings of The International Conference on Theology, Religion, Culture, and Humanities, 2024)
An acolyte, serving the priest during the Eucharist, plays a significant role in ensuring the smooth execution of the Eucharistic celebration, aiding the congregation in participating the Eucharist more devoutly. The Patron Saint of the acolytes is Saint Tarcisius, who dared to sacrifice himself to death to protect the Blessed Sacrament. Therefore, the acolyte needs to emulate Saint Tarcisius in carrying out his duties as an altar server. The acolytes at Saint Francis Xavier Parish, Kidul Loji, Yogyakarta lack a profound understanding of the patron of their ministry, leading to a deficiency in their representation during Eucharistic celebrations. This research aims to understand the extent to which the acolytes embody the spirituality of Saint Tarcisius, recognizing a gap in their knowledge about his life. Conducted descriptive qualitative research, this research focuses on active acolytes from Saint Francis Xavier Parish, totalling 20 individuals. Data collection involves observation, document study, and interviews. The findings revealed that a majority of the acolytes lacked a deep understanding of Saint Tarcisius's life story, resulting in a limited grasp of the spirituality he exemplified. In response to these findings, the researchers suggest that the parish should organize activities to familiarize acolytes with Saint Tarcisius and his spirituality. A proposed recollection activity aims to address these knowledge gaps, offering the acolytes a chance for spiritual enrichment and enthusiasm in carrying out their duties meaningfully. Keywords: spirituality; Saint Tarcisius; acolyte